Development of Multimedia Learning of Cell Material in Senior High School - Indah Purnamasari; Fadillah Fadillah; Warneri Warneri (STKIP Singkawang, 2020)
This study aims to describe the design of multimedia learning, to determine the feasibility and to determine the affective and psychomotor of students. The method in this research is the method of research and development or research and development using the 4D model, namely the definition, design and development. Participants of this study were biology subject teachers and students of class XI at SMA Negeri 2 Teluk Keramat. Data collection technique used observation, interview and documentation. Data were analyzed qualitatively and quantitatively. From the results of the validation of media experts, material experts and design experts obtained an average value of 4.33 with very valid criteria which means that multimedia learning is very feasible to use for field trials. Assessment of affective and psychomotor of students obtained an average of 3.5 and 3.6 with excellent criteria. From the results of product validation and testing that multimedia learning can help teachers in the learning process to create interesting learning for students.